Corporate Governance: Dividends, and Value - Lashgari, Malek (Journal of Applied Business and Economics, 2023)
As fair value of a business enterprise is a function of its earnings power, the more confident owners of equity are about their rights in controlling re investment or distribution of earnings, the higher is expected to be the equity value. Confidence will be high when managers provide full information about investments of the firm and equitable distribution of cash inflows to the stockholders. This is reinforced by business laws of the country. When investors are not well protected by the laws of the country, combined with a weak corporate governance, the market value of the internally generated cash and the stock value will decline, and investors would require an above average payout. Corporate governance structure of the firm, thereby, provides an explanation about the role of dividend policy of the firm and its impact on the value of equity. This is important as the role of dividend payment in determination of value of equity has been controversial.